Unveiling the Invisible Learning from Unpaid Household Work: Survey on Work and Lifelong Learning - Willa Lichun Liu (Adult Education Research Conference, 2007)
This paper explores the different dimensions of unpaid household work, and the informal learning involved in unpaid household work, and other non-work related activities. As part of a research project on Work and Lifelong learning (WALL), this paper draws its Data from a National Survey on Work and Learning (2004) done by the WALL research network, and compares them between different ethnic groups and recent immigrants, especially Chinese immigrants.